TRANSLATION BARRIERS IN COSMOS TERMINOLOGY - Khafiza Mukhtorova (TADQIQOTLAR.UZ, 2024)
Abstract: Language barriers have long posed significant challenges to the exchange of knowledge and ideas, especially in scientific fields. In the realm of astronomy, where the exploration of the cosmos captivates humanity's imagination, the need to bridge these barriers becomes even more crucial. This article explores the importance of overcoming language barriers in the quest for cosmic understanding. It highlights the impact of language diversity on astronomical research, education, and cross-cultural collaboration. The article discusses the challenges faced in bridging language barriers, such as translation accuracy, cultural nuances, and the role of technology. It emphasizes the transformative potential of multilingual collaborations, international scientific cooperation, and the development of accessible educational resources. By embracing diversity and fostering inclusive communication, humanity can unite in its collective pursuit of unraveling the mysteries of the cosmos.